Penerapan Aplikasi Microsoft Mathematics pada Pembelajaran Matematika bagi Siswa SMKS-9 Muhammadiyah Kota Bengkulu - Qurniati, Nofi; Prahasti (LPPM UNIKA Santo Thomas Medan, 2022)
This research is conducted based on observation that learning about mathematics in the class is always use convensional method. This research is sopposed to know learning outcomes in the application of learning Microsoft Mathematics application student SMKS - 9 Muhammadiyah Bengkulu. The methodology that is use in the research is Eksperimen Design with Randomized Control Group Only Design. The sample of this research is 81 student. Sample class is XI-2 and kelas XI-1 as an eksperimen class and control class. The data obtained were analyzed using thr t-test. Based on the result of the study, The average value of student understanding of learning outcomes by Microsoft Mathematics is 60,83 , while the conventional learning model is 48,29, value t = 2,67 and t = 1,65